Morphological development and growth of chub, Leuciscus cephalus (L.), larvae - Çalta, M (Blackwell Wissenschafts-Verlag Gmbh, 2000)
This study describes the morphological development and early growth of laboratory-raised chub, Leuciscus cephalus (L. 1758), larvae. Larvae hatched with relatively large yolk sacs, stayed motionless at the tank bottom and exhibited short and sudden bursts from time to time. They were olive in colour and with complete absence of melanophores on the body. Larvae were transparent but showed brownish eye pigment. Intense body pigmentation first appeared on day 4 after hatching. By day 8 the yolk sac was fully absorbed; only 30% of the initial population of larvae successfully established exogenous feeding. Fin rays first appeared on the dorsal and anal fins of larvae around day 12. Growth during the yolk sac stage was initially fast but slowed down with the increasing size of larvae at the time of yolk absorption. The specific growth rate (SGR) of larvae declined with time, although the total observation period was relatively short (12 days). SGR values ranged from 5.18 (day 2) to 2.97 (day 12). Only a negligible egg mortality was observed during the period of early endogenous feeding (between days 1 and 6), and about 45% towards the end of endogenous feeding and immediately after the yolk sac phase (between days 7 and 9). During the exogenous feeding period (between days 10 and 12) deaths were negligible.
Keywords: Swim Bladder Inflation; Subalpine Lake; Cyprinids; Teleostei; Muscles; Cohorts; Gills